2012
DOI: 10.1016/j.stem.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal-Stem-Cell-Induced Immunoregulation Involves FAS-Ligand-/FAS-Mediated T Cell Apoptosis

Abstract: SUMMARY Systemic infusion of bone marrow mesenchymal stem cells (BMMSCs) shows therapeutic benefit for a variety of autoimmune diseases, but the underlying mechanisms are poorly understood. Here we show that in mice systemic infusion of BMMSCs induced transient T-cell apoptosis via the Fas ligand (FasL)-dependent Fas pathway and could ameliorate disease phenotypes in fibrillin-1 mutated systemic sclerosis (SS) and dextran sulfate sodium-induced experimental colitis. FasL−/− BMMSCs did not induce T-cell apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
572
0
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 626 publications
(622 citation statements)
references
References 34 publications
30
572
0
5
Order By: Relevance
“…Although the mechanism by which IL-17 + MSCs upregulate Th17 cells is unknown, the interplay between donor MSCs and recipient microenvironment may determine MSC-based immunomodulatory response [33,41]. Our findings imply that MSC-based immunomodulation is regulated by different subsets of MSCs, in which they may exert either immunosuppressive or immunostimulatory functions.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although the mechanism by which IL-17 + MSCs upregulate Th17 cells is unknown, the interplay between donor MSCs and recipient microenvironment may determine MSC-based immunomodulatory response [33,41]. Our findings imply that MSC-based immunomodulation is regulated by different subsets of MSCs, in which they may exert either immunosuppressive or immunostimulatory functions.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies indicate that MSC-based immunotherapy is a promising therapeutic approach for a variety of autoimmune diseases, including systemic sclerosis and systemic lupus erythematosus [1,6,8,33]. However, the detailed mechanism of MSC-based immune therapy is not fully elucidated [34].…”
Section: Discussionmentioning
confidence: 99%
“…61 Activated MSCs can modulate adaptive immune cells through contact-dependent mechanisms. These include activation of the PD-1 pathway, 62 Fas-mediated T-cell apoptosis, 63 engagement of …”
Section: Immune Modulation By Mscsmentioning
confidence: 99%
“…Therefore, direct suppressive effects of MSCs on the immune system are short-lived, and do not explain the long-term therapeutic effects observed with MSCs in clinical and animal studies. In this context, it has been suggested that MSCs trigger a state of immune tolerance, for example, through the induction of regulatory T cells (Tregs) (6,7).…”
mentioning
confidence: 99%